Zoonotic potential of currently circulating avian influenza viruses Zoonotski potencijal trenutno cirkulirajućih virusa ptičje gripe - Savić, Vladimir, veterinar (2020)
Over the past and the current centuries, human influenza pandemics have been attributable to viruses with an avian ancestry. Birds are the main source of influenza A viruses and harbour a variety of antigenic subtypes. Certain avian influenza viruses are capable for cross-species transmission including human infections. Although sustained intrehuman transmission of such viruses has not been documented so far, each human infection with avian influenza viruses provides chances for the virus adaptation towards efficient transmission within human population. Here are reviewed currently circulating avian influenza viruses that are of major significance for public health.
Pandemije humane influence tijekom prošlog i ovog stoljeća pripisuju se virusima ptičjeg podrijetla. Ptice su glavni izvor virusa influence A i domaćini su različitim antigenskim podtipovima. Određeni virusi influence ptica imaju svojstvo prijenosa na različite vrste domaćina uključujući i ljude. Premda održivi interhumani prijenos takvih virusa do sada nije dokumentiran, svaka humana infekcija virusima influence ptica pruža im mogućnost prilagodbe prema učinkovitom prijenosu unutar ljudske populacije. Ovdje su razmotreni trenutno cirkulirajući virusi influence ptica koji su od najveće važnosti za javno zdravstvo.
Bibliografija: 65 jed.
Abstract ; Sažetak.
Keywords: Zoonoze -- Virus influence A -- Ptičja gripa -- H5N1 -- H7N9 -- H9N2